Effect of pay for performance to improve quality of maternal and child care in low- and middle-income countries: a systematic review - Ashis Das; Saji S. Gopalan; Daniel Chandramohan (BMC, 2016)
Abstract Background Pay for Performance (P4P) mechanisms to health facilities and providers are currently being tested in several low- and middle-income countries (LMIC) to improve maternal and child health (MCH). This paper reviews the existing evidence on the effect of P4P program on quality of MCH care in LMICs. Methods A systematic review of literature was conducted according to a registered protocol. MEDLINE, Web of Science, and Embase were searched using the key words maternal care, quality of care, ante natal care, emergency obstetric and neonatal care (EmONC) and child care. Of 4535 records retrieved, only eight papers met the inclusion criteria. Primary outcome of interest was quality of MCH disaggregated into structural quality, process quality and outcomes. Risk of bias across studies was assessed through a customized quality checklist. Results and discussion There were four controlled before after intervention studies, three cluster randomized controlled trials and one case control with post-intervention comparison of P4P programs for MCH care in Burundi, Democratic Republic of Congo, Egypt, the Philippines, and Rwanda. There is some evidence of positive effect of P4P only on process quality of MCH. The effect of P4P on delivery, EmONC, post natal care and under-five child care were not evaluated in these studies. There is weak evidence for P4P's positive effect on maternal and neonatal health outcomes and out-of-pocket expenses. P4P program had a few negative effects on structural quality. Conclusion P4P is effective to improve process quality of ante natal care. However, further research is needed to understand P4P's impact on MCH and their causal pathways in LMICs. Trial registration PROSPERO registration number CRD42014013077 .